Temporal system‐level organization of the switch from glycolytic to gluconeogenic operation in yeast - Guillermo G Zampar; Anne Kümmel; Jennifer Ewald; Stefan Jol; Bastian Niebel; Paola Picotti; Ruedi Aebersold; Uwe Sauer; Nicola Zamboni; Matthias Heinemann (Molecular Systems Biology, 2013)
Abstract The diauxic shift in Saccharomyces cerevisiae is an ideal model to study how eukaryotic cells readjust their metabolism from glycolytic to gluconeogenic operation. In this work, we generated time‐resolved physiological data, quantitative metabolome (69 intracellular metabolites) and proteome (72 enzymes) profiles. We found that the diauxic shift is accomplished by three key events that are temporally organized: (i) a reduction in the glycolytic flux and the production of storage compounds before glucose depletion, mediated by downregulation of phosphofructokinase and pyruvate kinase reactions; (ii) upon glucose exhaustion, the reversion of carbon flow through glycolysis and onset of the glyoxylate cycle operation triggered by an increased expression of the enzymes that catalyze the malate synthase and cytosolic citrate synthase reactions; and (iii) in the later stages of the adaptation, the shutting down of the pentose phosphate pathway with a change in NADPH regeneration. Moreover, we identified the transcription factors associated with the observed changes in protein abundances. Taken together, our results represent an important contribution toward a systems‐level understanding of how this adaptation is realized.